Outcomes of Problem-based Learning (PBL) Implementation from Students’ Perspectives - Mohd. Yusof, Khairiyah; Abd. Hamid, Mohd. Kamaruddin; Abu Hassan, Mohd. Ariffin; Hassim, Mimi Haryani; Syed Hassan, Syed Ahmad Helmi; Tasir, Zaidatun (2005)
Problem-based Learning (PBL) is known to develop and enhance generic skills. The prevailing question is whether the same benefits can be seen for “passive” Malaysian students. In the 2004/05-2 semester, fourth year chemical engineering undergraduates who took Process Control and Dynamics, which was taught using PBL, were surveyed at the end of the semester to assess the generic skills outcomes. The result was overwhelmingly positive, with most of them agreeing or strongly agreeing that PBL had developed or improved their generic skills. The outcome of this study had positively shown that PBL was just as effective even in the supposedly passive Malaysian education culture.